Decellularization techniques: unveiling the blueprint for tracheal tissue engineering - Gomes, Keisha T.; Prasad, Palla Ranga; Sandhu, Jagnoor Singh; Kumar, Ashwini; Kumar, Naveena A. N.; Shridhar, N. B.; Bisht, Bharti; Paul, Manash K. (Frontiers in Bioengineering and Biotechnology, 2025)
Certain congenital or acquired diseases and defects such as tracheo-oesophageal fistula, tracheomalacia, tracheal stenosis, airway ischemia, infections, and tumours can cause damage to the trachea. Treatments available do not offer any permanent solutions. Moreover, long-segment defects in the trachea have no available surgical treatments. Tissue engineering has gained popularity in current regenerative medicine as a promising approach to bridge this gap. Among the various tissue engineering techniques, decellularization is a widely used approach that removes the cellular and nuclear contents from the tissue while preserving the native extracellular matrix components. The decellularized scaffolds exhibit significantly lower immunogenicity and retain the essential biomechanical and proangiogenic properties of native tissue, creating a foundation for trachea regeneration. The present review provides an overview of trachea decellularization advancements, exploring how recellularization approaches can be optimized by using various stem cells and tissue-specific cells to restore the scaffold’s structure and function. We examine critical factors such as mechanical properties, revascularization, and immunogenicity involved in the transplantation of tissue-engineered grafts.